2021
DOI: 10.3390/jrfm14060277
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Causal Linkages among Inflation, Interest Rate, and Economic Growth in Pakistan under the Influence of COVID-19 Pandemic: A Wavelet Transformation Approach

Abstract: This research is the earliest attempt to understand the impact of inflation and the interest rate on output growth in the context of Pakistan using the wavelet transformation approach. For this study, we used monthly data on inflation, the interest rate, and industrial production from January 1991 to May 2020. The COVID-19 pandemic has affected economies around the world, especially in view of the measures taken by governmental authorities regarding enforced lockdowns and social distancing. Traditional studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 62 publications
(67 reference statements)
2
25
0
1
Order By: Relevance
“…The COVID-19 pandemic caused catastrophic impacts on the stock market worldwide, causing wide economic disruptions, investment decision delays and decreased in business profits [ 85 ]. This globally devastating impact has been reported by [ 86 , 87 ] as well.…”
Section: Literature Reviewmentioning
confidence: 69%
“…The COVID-19 pandemic caused catastrophic impacts on the stock market worldwide, causing wide economic disruptions, investment decision delays and decreased in business profits [ 85 ]. This globally devastating impact has been reported by [ 86 , 87 ] as well.…”
Section: Literature Reviewmentioning
confidence: 69%
“…As a result, there are different views between the interest rate and economic growth (Sert, 2021). Studies on the relationship between interest rate and economic growth (Blanchard and Summers, 1984;McKinnon, 1989;Barro and Sala-iMartin, 1990;Schächter and Stokman, 1995;Udoka and Roland, 2012;Greenwood et al, 2013 ;Padhi, 2018;Lee and Werner, 2018;Ogege, 2019;Hayat et al, 2021) it is seen that there are different effects between the related variables.…”
Section: The Effect Of Interest Rates On Economic Growthmentioning
confidence: 99%
“…In the econometric analysis, the coefficient R2 = 0.999 reflects the high degree of determination with a prediction accuracy of approximately 99.9%. Hayat et al (2021) suggested that economic growth represents the capacity of a certain country to increase its level of output. Easterly and Rebelo (1993) consider that a large majority of the growth models forecast the fact that taxes on investment and income exhibit destructive impact on growth.…”
Section: Literature Reviewmentioning
confidence: 99%